Utilization of muscovado sugar in tamarind jelly-making - Escaner, Rojeanie P. (2000.)
The feasibility of utilizing muscovado sugar for tamaring jelly production was investigated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tamarind jelly making